بنية التوازي في "أخي جاوزالظالمون المدى " -مقاربة أسلوبية - بن عافية, وداد (قــــــراءات, 2019)
ملخص : تهدف هذه الدراسة إلى استقصاء كيفية تبنين النص الشعري وتحقيق انسجامه الداخلي من خلال مبدأ التوازي الذي لا يعتبر ظاهرة أسلوبية خارجية، بل هو مبدأ تركيبي وعنصر مهم في إنتاج الدلالة، وذلك من خلال مقاربة قصيدة "أخي جاوز الظالمون المدى" للشاعر علي محمود طه وتتبع تمظهرات التوازي في أنواعه المتعددة: التوازي الصوتي، التوازي الصرفي، التوازي الدلالي. لتخلص الدراسة إلى أن التشابه هو المبدأ الأساسي لظاهرة التوازي البلاغية وليس التطابق التام، وهو ما انعكس على دلالة القصيدة التي تصب في معنى المقاومة والتحدي. Summary : This study aims at enquiring the way imagery in poetry is structured in order to realize its internal coherence through parallelism principle which is not considred as an external stylistic phenomenon; however, it is a structural principle and an indispensable element as well , in the semantical production, as seen through approaching"Alimahmoud’s" poem, following parallelism in its numerous forms such as:semanticparallelism, phorologicalparallelism and syntqcticparallelism. The study concludes that the similarity is the most important principle of the eloquence parallelism phenomenon,and its not the entire conform which is reflected on the sense of the poet that concerned with the concepts of resistance and challenge